New roles for old friends: a microtubule-localized COP1-interacting protein promotes hypocotyl elongation in the dark - Arico, Denise Soledad (2019)
Plant irritability for light stimuli becomes crucial to cope with ambient fluctuations in order to keep up homeostasis and accomplish the life cyclesuccessfully. Light environment governs plant development. Perception of light is carried out by photoreceptors, such as phytochromes (phyA to phyE) that absorb primarily in red and far-red; and cryptochromes (cry1 to cry3) that are predominantly blue-light receptors. Once perceived, plants are able to integrate light signals into biochemical networks that conduce to proper response. Transducing these lightsignals involve changes in the phosphorylation state of proteins. In an early light-induced phosphoproteome study in Arabidopsis thaliana, we identified a protein that presents light-responsive dephosphorylation in the presence of photoactivated photoreceptors. This protein was particularly interesting because it was reported to interact with the key repressor of photomorphogenesis COP1 and thus, it is potentially involved in early photomorphogenesis events. In vivo assays with a transcriptional reporter revealed it is expressed in cotyledons and elongation zones of hypocotyl and root. Its expression is regulated negatively by light. CRISPR-CAS9 mutated lines exhibit shorter hypocotyls in darkness. Confocal microscopy assays with stably transgenic lines expressing translational reporters revealed localization to cortical microtubules. We are currently studying the biological implications of its microtubule association and its regulation by COP1 through changes in phosphorylation patterns. All these results suggest this protein promotes growth in darkness by affecting microtubules dynamics.